Search Computing Challenges and Directions - Ceri, Stefano; Brambilla, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Search computing, which has evolved from service computing, focuses on building the answers to complex search queries by interacting with a constellation of cooperating search services, using ranking and joining of results as the dominant factors for service composition. The field is multi-disciplinary in nature, and takes advantage of contributions from other research areas such as knowledge representation, human-computer interfaces, psychology, sociology, economics and legal sciences. The book is divided into three parts. The first part includes some visionary contributions on the latest trends in search, which is becoming increasingly task-oriented and is starting to use ontological knowledge in order to manage complex queries. The second part explores background and related technologies, which can be considered as parallel fields of research, useful both for setting the theoretical premises for search computing and for providing a technological framework for building search computing systems and applications. The third part delves into the conceptual and technological problems and issues arising when dealing with search computing as a new search paradigm. It provides a unified view of the results of the Search Computing project as achieved exactly one year after its starting date.
Visions -- 1: Search Computing -- 2: Next Generation Web Search -- 3: Search for Knowledge -- Technology Watch for Search Computing -- 4: The Search Engine Industry -- 5: From Mashup Technologies to Universal Integration: Search Computing the Imperative Way -- 6: Web Data Extraction for Service Creation -- 7: Dataspaces -- 8: Multimedia and Multimodal Information Retrieval -- Issues in Search Computing -- 9: Service Marts -- 10: Join Methods and Query Optimization -- 11: Rank-Join Algorithms for Search Computing -- 12: Panta Rhei: Flexible Execution Engine for Search Computing Queries -- 13: Liquid Queries and Liquid Results in Search Computing -- 14: Building Search Computing Applications -- 15: Search Computing and the Life Sciences -- Appendix A: Search Computing Dictionary.
Keywords: Computer science; Software engineering; Information theory; Computer software; Data mining; Information systems; Computer Science; Information Systems Applications (incl.Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Programming Techniques; Data Mining and Knowledge Discovery; Theory of Computation